Students' Emotional and Social Engagement in Jigsaw-Based Marriage Learning at SMAN 3 Sidoarjo - Sahila Faradisa; Moh Faizin (Institut Agama Islam Negeri Pontianak, 2025)
Learning activities in Islamic Religious Education (PAI), particularly on the topic of Marriage in Islam, have traditionally focused on cognitive understanding such as legal provisions and formal requirements. However, marriage carries broader emotional, social, and moral dimensions that are relevant to the developmental stage of high school students who are exploring identity and interpersonal relationships. This study aims to describe students' emotional and social engagement through the implementation of the Jigsaw cooperative learning model in teaching the topic of marriage at SMA Negeri 3 Sidoarjo. This research employed a qualitative descriptive design. The participants consisted of a PAI teacher and eleventh-grade students involved in Jigsaw-based learning. Data were collected through classroom observations, semi-structured interviews with teachers and students, and document analysis involving lesson modules, group worksheets, and observation notes. Data analysis followed the Miles, Huberman, and Saldana model, which includes data condensation, data display, and conclusion drawing. Data credibility was ensured through source triangulation (teachers, students, documents) and technique triangulation (observation, interview, documentation). The findings reveal that the Jigsaw model effectively enhances students’ emotional engagement, indicated by the emergence of empathy, self-reflection, and awareness regarding marital responsibilities. Social engagement also increased, as shown through active interactions, cooperation, peer support, and greater willingness to express opinions. Additionally, students’ roles as “content experts” fostered academic and social responsibility within their groups. Overall, the study concludes that the Jigsaw model strengthens affective aspects of PAI learning and serves as a strategic alternative for character development in secondary school students.